Application of methodological strategies for an effective speaking skill learning of the students of second year of high school. - Peláez Luján, Francois Michel (Machala : Universidad Técnica de Machala, 2015)
El presente trabajo investigativo tiene como objetivo dotar con herramientas teóricas al docente para aplicarlas como metodologías y alcanzar un desarrollo constante en la habilidad de hablar en los estudiantes de segundo de bachillerato.
The objective of this research paper is to award with theoretical resources to the teacher to apply as methodologies, and reach a constantly speaking skill development in the students of second year of high school.
Keywords: ESTRATEGIA METODOLOGICA; HABILIDAD; APRENDIZAJE; ESTUDIANTE